The Role of Malaria Parasite Biomass and Immunohaematological Indices in the Pathogenesis of Severe Malaria among Children in Accra Metropolis of Ghana - Addison, T.K. (University Of Ghana, 2017)
The pathogenesis of severe complications of Plasmodium falciparum malaria is still poorly understood in spite of its potentially fatal consequences. This poses practical challenges for malaria control efforts, especially, in discriminating children who are really at risk of severe malaria from those with incidental malaria in moderate and high malaria transmission areas. The search for reliable diagnostic and prognostic biomarkers for severe malaria is yet to produce encouraging results and this gives impetus to the pursuit of diagnostic/prognostic markers from perspective of little-explored indices like parasite biomass and composite malariometric index. This study explored the prognostic value of parasite biomass and immunohaematological indices in discriminating malaria phenotypes. A total of 172 Ghanaian children aged 1 to 12 years with cerebral malaria (46), severe malarial anaemia (23), uncomplicated malaria (46) and healthy controls (57) in the Greater Accra metropolis were recruited. Giemsa stained slides were enumerated using microscopy and plasma HRP2 concentrations were measured using ELISA. Haematological indices were measured using Sysmex Automated Haematology Analyser and CD4 and CD8 counts were enumerated using a FACSCalibur. Total parasite biomass, circulating parasite biomass and sequestered parasite biomass estimates for each patient was evaluated from the plasma histidine-rich protein 2 (HRP2) concentration as well as haematocrit, patient’s body weight and parasite density using a mathematical model. Principal Component Analysis (PCA) approach was employed in the construction of a composite malariometric index using parasitological and immunohaematological variables. A receiver operating characteristic curve was used in assessing
Thesis (MPhil.)
Keywords: Malaria; Parasite; Immunohaematological Indices; Pathogenesis; Plasmodium falciparum; Ghana